(untitled) (Nóema, 2014)
This analysis is focused on the concept of truth, which is intended as praxis and code of behaviour according to which the philosopher shapes his existence. Such matter is developed in the domain of ancient cynicism as well as of contemporary philosopher Carlo Sini. These two perspectives are put in contact. Michel Foucault’s speculation is an important instrument to articulate these two theories. In accordance with the French philosopher’s understanding, the criterion according to which the different forms of truth are analyzed is the consideration of the way they affect the subject’s behaviour. Such procedure questions our way to approach truth and philosophical practice.